Education and Alteration. Notes on Personalism, Alterity and Education in Dialogue with Michel de Certeau - Rovea, Federico (Paedagogia Christiana, 2021)
This article tries to elaborate some insights from Michel de Certeau’s works on personalism, alterity and education. The aim is to add a poorly known voice to the contemporary debate around pedagogy and personalism. De Certeau’s original account of personhood, based on the movement of ‘alteration’ rather than on ‘identity’, is presented as original and useful to enrich the contemporary educational debate. The article firstly analyzes two texts where Certeau deals specifically with the role of alterity in educational contexts. The uncanny and ungraspable movement of ‘alteration’ will be shown as fundamental in the person’s formation. Secondly, it will be argued that such account of alterity is rooted in Certeau’s interpretation of the Christian tradition. Finally, it will be maintained the possibility of conceiving education itself as a process of ‘alteration’.